Low birth weight and dental cares: is theree any association? - Wan Salina W.S.; Nizam A; Naing, L (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Low birth weight is defined as the newborn weighing less than 2500 g and it is a major public health problem While a long list of mortality and morbidity conditions have been associated with low birth weight, dental conditions have not received much attention. Most of the study looks at relationship between low birth weight and enamel defects. The aim of this study was to determine the association between low birth weight and dental canes among 6-year-old school children in Tumpat district, Kelantan. Methodology: This is a case-control study. By using simple random sampling 473 16-year-old school children from nine schools in Tumpat district were recruited into this study. Based on clinical examination, subjects were categorized into three groups that were caries free, mild caries and high caries group. Weight at birth was identified based on birth certificate which was obtained by asking the children to take the questionnaire home to be filled up by parents. The data analysis involved ordinal logistic regression adysis. Results: Results showed that there was no significant dzzerence of caries level in subjects with n~rmabli rth weight and low birth weight with p=0.317. Conclusion: This study failed the find any association between the low birth weight and dental caries among 16-year-old subjects in Tumpat district. Further study is needed to determine other factors that may be associated with development of dental caries in this group.